Biotic factors drive bacterioplankton community in a tropical coastal site of the equatorial atlantic ocean - Kavagutti, Vinicius Silva (Universidade Federal de São Carlos, 2016)
The relationship between latitude and microbial diversity in the ocean is controversial. Niche models predict higher richness at high latitudes in winter, while snapshot field-sampling point towards higher richness at intermediate latitudes, with lower values both towards equatorial and Polar Regions. However, given the dynamic nature of ocean’s ecosystem it is difficult to account for temporal variations in empirical assessments of microbial biodiversity. Here, we compared the components of diversity (richness and evenness) and microbial population stability (coefficient of variation) in two coastal ocean observatories with similar trophic state located in contrasting latitudes, one located in the Equatorial Atlantic Ocean, and one temperate located in the Northwestern Mediterranean Sea, to evaluate which factors drive the dynamics of microbial communities in each site. Our observations support the view that, as animals and plants, microbial communities exhibit higher (or at least similar) richness towards the equator, at least in the coastal ocean. We also found evidence of increasing stability with increasing evenness in tropical microbial communities when compared to the temperate ones. Temperature and silicates drove temperate free-living prokaryotic communities, while tropical ones were driven by stochastic factors such as biotic interactions with eukaryotes. We propose a conceptual framework where microbial community composition would be driven by deterministic factors in higher latitudes and once the factor temperature is removed moving towards the equator, more stochastic factors such as biotic interactions would emerge as the main factors shaping microbial communities. This study highlights the importance of comparative studies on Eulerian time-series distributed at different latitudes to fully understand the diversity patterns of microbial communities in the ocean.
Keywords: Diversidade bacteriana; Gradiente latitudinal; Séries temporais; Amostragem Euleriana; Sequenciamento de nova geração; Bacterial diversity; Latitudinal gradient; Time series; Eulerian sampling; Next generation sequencing; CIENCIAS BIOLOGICAS::ECOLOGIA